Simulations about Stability, Damage, and Heating Impacts for an X-ray Optical Delay Line at SASE3. Issue 1 (1st December 2022) - Tavakkoly, Marziyeh; Grünert, Jan; Koch, Andreas; La Civita, Daniele; Makita, Mikako; Meyer, Michael; Planas, Marc; Serkez, Svitozar; Sinn, Harald; Wohlenberg, Torsten; Vannoni, Maurizio
Abstract: European XFEL has initiated a project to facilitate two-color pump-probe spectroscopy with X-rays at the SASE3 soft X-ray undulator. To this end, the controllable temporal delay between the two X-ray pulses is obtained by a magnetic chicane and an optical delay line (ODL) that delay the electron and X-ray beams, respectively. This article focuses on describing the alignment process of the ODL and its related specification. The distance between the experimental station and the ODL is nearly 500 m, thus if one of the mirrors in the ODL is misaligned, the focus spot experiences a noticeable shift. Moreover, a pulse train can include up to 2700 X-ray pulses with a minimum spacing of 222 ns. An increase in temperature per pulse would just add up if there was no heat removal during that time and the material could be damaged during a pulse train. The question arises whether the X-ray optics can survive the high X-ray peak power during a single pulse. Finally, the present study also investigates the damage issue.